2000
DOI: 10.1093/gerona/55.4.b183
|View full text |Cite
|
Sign up to set email alerts
|

Estriol (E3) Replacement Improves Endothelial Function and Bone Mineral Density in Very Elderly Women

Abstract: We investigated the effects of estriol (E3) on endothelial function and bone mineral density (BMD) in very elderly women. Twenty-four very elderly women (80 +/- 3.5 years old) were administered CaCl2 with or without estriol treatment (2 mg/day) for 30 weeks (hormone replacement treatment [HRT] group vs control group). Endothelium-dependent flow-mediated dilatation (FMD), endothelium-independent dilatation by nitroglycerin of the brachial artery, and BMD were assessed. Levels of plasma lipids and apoproteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This study has shown that hormones and exercise interact to influence bone adaptations, and thus raise E 3 level related to increased BMD following exercise in female athletes. For example, serum E 2 , cortisol, PTH and T 3 levels in the athlete group were higher than those of the controls, and the major finding of this study was that increased radius BMD (K<0.05) and calcaneus BMD (K<0.01, P<0.05) were significantly and positively related to serum E 3 (K<0.01, P<0.01) concentrations [10][11][12] . Therefore, a clear understanding the interaction suggested by the present data between E 3 concentration and the adaptation of bone to exercise is important, and provides an interaction through which the estrogen receptors involved in the early response of bone cells might increase their responsiveness to loading [11,12] .…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…This study has shown that hormones and exercise interact to influence bone adaptations, and thus raise E 3 level related to increased BMD following exercise in female athletes. For example, serum E 2 , cortisol, PTH and T 3 levels in the athlete group were higher than those of the controls, and the major finding of this study was that increased radius BMD (K<0.05) and calcaneus BMD (K<0.01, P<0.05) were significantly and positively related to serum E 3 (K<0.01, P<0.01) concentrations [10][11][12] . Therefore, a clear understanding the interaction suggested by the present data between E 3 concentration and the adaptation of bone to exercise is important, and provides an interaction through which the estrogen receptors involved in the early response of bone cells might increase their responsiveness to loading [11,12] .…”
Section: Discussionmentioning
confidence: 49%
“…For example, serum E 2 , cortisol, PTH and T 3 levels in the athlete group were higher than those of the controls, and the major finding of this study was that increased radius BMD (K<0.05) and calcaneus BMD (K<0.01, P<0.05) were significantly and positively related to serum E 3 (K<0.01, P<0.01) concentrations [10][11][12] . Therefore, a clear understanding the interaction suggested by the present data between E 3 concentration and the adaptation of bone to exercise is important, and provides an interaction through which the estrogen receptors involved in the early response of bone cells might increase their responsiveness to loading [11,12] . These results indicate that physical exercise positively affects the maintenance of radius BMD (K<0.05), calcaneus BMD (K<0.01, P<0.05) in female athletes, thus increased E 3 level can prevent BMD loss and possible risk of osteoporosis [12] .…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations